PENERAPAN SHINVA OEE MONITORING SYSTEM UNTUK MENINGKATKAN OEE DI PT. MAKMUR JAYA ABADI - Falwaguna, Muhammad Salka; Ihsan, Tiaradia (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
The concept of OEE is a method for measuring the effectiveness of machines or production equipment that involves three main factors: Availability, Performance, and Quality. The OEE calculation formula is the product of these three factors. A case study at PT. Makmur Jaya Abadi shows that the implementation of the OEE Monitoring System has provided real benefits, such as improved production efficiency, improved product quality, and reduced production costs. However, the challenges faced include system complexity, training needs, and changes in work culture.